STUDI PENENTU DAYA SAING TERHADAP INVESTASI PADA INDUSTRI MEBEL DI KABUPATEN JEPARA - Sisno Riyoko (Universitas Islam Nahdlatul Ulama Jepara, 2012)
AbstractThe study aims to find out, describing the identification and testing of the determinant of competitiveness to improve company performance and competitiveness to test the influence of investment. The results showed that the multilevel determinants of competitiveness include the future companies ability to provide product according to market need, company policies, vision and mission of the company, production process, price and design, product development, expects demand growth, professional, production machine, Cooperation with overseas, research funding sources, andcooperation withuniversities. Testing the hypothesis of the independent variable of competitiveness on the dependent variable of investment concluded that the Ha received.Based on the result of research that the main determinants affecting the competitiveness of the extent to which companies can meet the market demand based on consumer demand. For that companies must improve their performance in addition to these to support the competitiveness of the local government should make policies the support therealization of policy of competitiveness. Keywords: competitiveness, determinant of competitiveness, investment, furniture Abstrak Penelitian ini bertujuan untuk menemukan, mengidentifikasi dan menguji penentu daya saing untuk memperbaiki kinerja dan daya saing perusahaan dan menguji pengaruhnya pada investasi. Hasil penelitian memperlihatkan bahwa penentu daya saing meliputi kemampuan perusahaan menyediakan produk sesuai kebutuhan pasar, kebijakan perusahaan, visi dan misi perusahaan, proses produksi, harga dan desain, pengembangan produk, harapan pertumbuhan permintaan, tenaga ahli, mesin produksi, kerjasama dengan perusahaan luar negeri, sumber pendanaan untuk penelitian, dan kerjasama dengan lembaga pendukung (perguruan tinggi). Hasil pengujian hipotesis dari model regresi dengan variabel independen daya saing dan variabel dependen investasi memperlihatkan bahwa daya saing berpengaruh terhadap investasi. Berdasarkan hasil penelitian bahwa faktor utama penentu daya saing adalah kemampuan perusahaan memenuhi kebutuhan pasar, maka perusahaan harus selalu berusaha untuk mengikuti trend yang berkembang. Sedangkan pemerintah daerah harus membuat kebijakan untuk mendukung saya saing industri mebel.Kata kunci: daya saing, penentu daya saing, investasi, industri mebel